TEACHING CONFIDENCE IN FOCUS: PSYCHOLOGICAL COMPETENCE AMONG PRESERVICE TEACHERS - Liah Rosdiani Nasution; Sandi Pradana (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2025)
Teacher education programs are instrumental in equipping future educators with the necessary skills to excel in their roles. This study investigates the effectiveness of teaching programs at UIN Syahada and their contribution to developing preservice teachers’ psychological competence. The research employs a quantitative approach, examining correlations between program effectiveness and psychological competence to assess the impact of structured training. Findings reveal a positive correlation (r = 0.503) between teaching program effectiveness and psychological competence; however, the relationship is not statistically significant (p = 0.431). These results highlight the potential influence of program design and external factors in shaping psychological competencies. The study underscores the importance of integrating psychological literacy into teacher training programs, providing actionable recommendations to enhance curriculum development and foster well-rounded educators capable of addressing complex classroom dynamics.